BORRA DE PRÓPOLIS NA PROTEÇÃO E SANITIZAÇÃO DE OVOS PARA CONSUMO - Alves, Mirela Fernanda; De Moraes, Elis Regina; De Ramos, Laura; De Souza, Danilo; Serra, Roberto Henrique; Pucheta, Renata (ANAIS DO ENIC, 2018)
-